KINERJA KARYAWAN DITINJAU DARI ETOS KERJA, BUDAYA ORGANISASI, DAN KECERDASAN EMOSIONAL PADA DINAS PERDAGANGAN KOTA SURAKARTA - Fitri Ita Muniroh; Sudarwati Sudarwati; Istiqomah Istiqomah (STEKOM PRESS, 2021)
This research aims to see employee feelings in terms of organization, organization, and emotional intelligence at the Surakarta City Trade Office. The sampling technique used purposive sampling technique which resulted in a sample of 45 employees. Techniques for obtaining data using questionnaire techniques. The research method with data analysis techniques using validity, reliability, classical assumptions, multiple regression analysis and hypothesis testing. The results showed that simultaneously work ethic, organizational culture, and intelligence had a positive and significant effect on employee performance while partially work ethic had no effect on employee performance in the organization group and emotional intelligence had an effect on employee performance.